2022
DOI: 10.1111/ctr.14845
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning‐based prediction of mortality after heart transplantation in adults with congenital heart disease: A UNOS database analysis

Abstract: Background Machine learning (ML) is increasingly being applied in Cardiology to predict outcomes and assist in clinical decision‐making. We sought to develop and validate an ML model for the prediction of mortality after heart transplantation (HT) in adults with congenital heart disease (ACHD). Methods The United Network for Organ Sharing (UNOS) database was queried from 2000 to 2020 for ACHD patients who underwent isolated HT. The study cohort was randomly split into derivation (70%) and validation (30%) data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“… 3 A multitude of studies have implicated kidney dysfunction as one of the most important risk factors for death in adults with congenital heart disease, increasing the risk of death by 2‐ to 3‐fold. 4 , 5 , 6 Similar findings have been confirmed within the subgroup of patients with Fontan circulation. 7 Despite widespread availability as key screening tools for chronic kidney disease (CKD), data regarding estimated glomerular filtration rate (eGFR) and urine albumin‐to‐creatinine ratio (ACR) in patients with Fontan circulation remain limited.…”
supporting
confidence: 76%
“… 3 A multitude of studies have implicated kidney dysfunction as one of the most important risk factors for death in adults with congenital heart disease, increasing the risk of death by 2‐ to 3‐fold. 4 , 5 , 6 Similar findings have been confirmed within the subgroup of patients with Fontan circulation. 7 Despite widespread availability as key screening tools for chronic kidney disease (CKD), data regarding estimated glomerular filtration rate (eGFR) and urine albumin‐to‐creatinine ratio (ACR) in patients with Fontan circulation remain limited.…”
supporting
confidence: 76%
“…23 A recent study showed that Catboost (a gradient-boosting algorithm) can predict the posttransplant mortality rate of adults with congenital heart disease, with an AUC value of 0.80. 24 In these four models, the performance of identifying highrisk populations for CHD was very similar. SVM has the best performance (AUC ¼ 0.898), whereas other models (logistic regression, AUC ¼ 0.895; random forest, AUC ¼ 0.894; XGBoost, AUC ¼ 0.891) can provide similar results.…”
Section: Discussionmentioning
confidence: 93%
“…Mohan et al constructed a mixed machine learning technique based on linear models and random forest to predict heart disease, with an accuracy of 88.7% 23 . A recent study showed that Catboost (a gradient-boosting algorithm) can predict the posttransplant mortality rate of adults with congenital heart disease, with an AUC value of 0.80 24 …”
Section: Discussionmentioning
confidence: 99%
“…Prediction models are central to healthcare research and practice. In cardiology, ML-based prediction models are gaining traction for forecasting outcomes and supporting clinical decisions [ 14 , 15 ]. For instance, these models have been employed to predict mortality following heart transplantation in adults with congenital heart disease, aiding physicians in personalized treatment strategies [ 15 ].…”
Section: Reviewmentioning
confidence: 99%
“…In cardiology, ML-based prediction models are gaining traction for forecasting outcomes and supporting clinical decisions [ 14 , 15 ]. For instance, these models have been employed to predict mortality following heart transplantation in adults with congenital heart disease, aiding physicians in personalized treatment strategies [ 15 ]. While AI holds immense potential in healthcare, including pediatric cardiology, there is still a need for further research to develop models that are interpretable, reliable, and applicable to a diverse range of complex CHD cases.…”
Section: Reviewmentioning
confidence: 99%